The Manifestation of Discursive Devices in Male and Female Politician Speeches: A Socio-Cognitive Study - Othman, Arazoo R.; Salih, Salah M. (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract: Critical Discourse Analysis (CDA) is a form of discourse analytical study that focuses on how text and language in the social and political context enact, perpetuate, and oppose social power abuse, domination, and inequality. Critical discourse analysts take an explicit position in such dissident research, and so seek to analyze, expose, and ultimately oppose social injustice. This study examines four political speeches made by male and female politicians (Boris Johnson, Jill Biden, Jeanine Hennis-Plasschaert, Justin Trudeau). Adopting Van Dijk's Socio-Cognitive Model (2005), this article focuses on examining various ideologies and attitudes by analysing male and female politicians' speeches to see how they attempt to defend their opinions and persuade their audience. The linguistic analysis of the speeches reveals the way how male and female politicians disseminate or express their beliefs differently. The results of the investigation indicate that devices such as "actor description, authority, illustration/example, generalization, national self-glorification, and norm expression" are used to show positive self-representation while devices such as "burden, comparison, euphemism, implication" are used to show negative other representation. Also, those who use these devices more often tend to speak more formally and with stronger ideological biases in their discourse. So, they start using more sophisticated discursive strategies, frameworks, and rhetorical tools in a new way. And that Female politicians use discursive devices distinct from those employed by Male politicians. Key Words: discursive devices, socio-cognitive, micro-level structure, macro-level structure.